Path Analysis on the Effects of Motivation and Other Factors on Midwives Performance of Preeclampsia Management in Malang, East Java - Nicky Danur Jayanti; Didik Tamtomo; Endang Sutisna Sulaeman (Masters Program in Public Health, Sebelas Maret University, 2017)
Background: The incidences of preeclampsia and eclampsia remain high worldwide. Preeclampsia and eclampsia remain a major cause (31.04%) of maternal mortality in East Java. It is essential to early detect preeclampsia in order to prevent mortality. Good performance of midwives in the management of preeclampsia may reduce maternal mortality attributable to eclampsia. It is hypothesized that motivation, leadership style, working atmosphere, insentive, skill, and training, all have impact on midwives performance. This study aimed to analyze the effects of motivation and other factors on midwives performance in preeclampsia management in Malang, East Java, using path analysis model.Subjects and Method: This was an analytic observational study with cross sectional design. The study was conducted in Community Helath Centers, Malang, East Java in September 2017. A total sample of 161 midwives were selected using total sampling technique. The endogenous variables were motivation and midwives performance. The exogenous variables were insentive, working atmosphere, leadership style, skill and training. The data were collected using a set of questionnaire and analyzed by path analysis.Results: Midwife performance were positively affected by working atmosphere (b= 0.11; SE=0.04; p= 0.004), leadership style (b= 0.06; SE= 0.02; p= 0.004), skill (b= 0.24; SE= 0.03, p<0.001), and motivation (b= 0.68; SE= 0.03; p<0.001). Motivation was positively afected by insentive (b= 0.25; SE= 0.09, p= 0.006), training (b= 0.89; SE= 0.28; p= 0.001), skill (b= 0.39; SE= 0.06; p<0.001), leadership style (b= 0.08; SE= 0.05; p= 0.110), and working atmosphere (b= 0.35; SE= 0.09; p<0.001).Conclusion: Midwives performance are positively affected by working condition, leadership, skill, and motivation.Keyword: preeclampsia, path analysis, motivation, midwives performanceCorrespondence: Nicky Danur Jayanti. Masters Program in Public Heath, Sebelas Maret University, Jl. Ir. Sutami 36 A, Surakarta 57126, Central Java. Email: nicky_daanty@yahoo.co.idJournal of Health Policy and Management (2017), 2(2): 137-146https://doi.org/10.26911/thejhpm.2017.02.02.05